2015
DOI: 10.3109/19401736.2015.1089550
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of the Vespa mandarinia Smith (Hymenoptera: Vespidae: Vespinae) and a phylogenetic analysis of the Vespoidea

Abstract: We report the mitochondrial genome of the Vespa mandarinia Smith (GenBank accession no. KR059904) for the subfamily Vespinae (Hymenoptera: Vespidae). This is the first completely sequenced mitochodrial genome from the genus Vespa. All of the typical mitochondrial genes were sequenced with a length of 15 902 bp. In the V. mandarinia mitochondrial genome, four rearrangement events occurred compared with the pupative ancestral arrangement of insects, corresponding to the shuffling of trnQ and trnM, translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…With regard to Vespidae, a strong sister relationship between Vespinae and Polistinae (BPP = 1; ML, 100 %) was obtained, with the placement of Eumeninae as the basal lineage. Consistent results for these relationships have previously been reported (Chen et al ; Wei et al ). Within Vespa , the sister relationship between V. ducalis and V. mandarinia —leaving V. bicolor as sister to the other two Vespa species—was strongly supported (BPP = 1; ML, 94 %).…”
Section: Resultssupporting
confidence: 91%
“…With regard to Vespidae, a strong sister relationship between Vespinae and Polistinae (BPP = 1; ML, 100 %) was obtained, with the placement of Eumeninae as the basal lineage. Consistent results for these relationships have previously been reported (Chen et al ; Wei et al ). Within Vespa , the sister relationship between V. ducalis and V. mandarinia —leaving V. bicolor as sister to the other two Vespa species—was strongly supported (BPP = 1; ML, 94 %).…”
Section: Resultssupporting
confidence: 91%
“…The other ten pairs of genes were directly adjacent to each other. In both species, the length of the mitochondrial genome and overlapping regions between genes was normal, while the intergenic spacer is considerably longer than other Vespoidea mitochondrial genomes [22,34,35,36]. …”
Section: Resultsmentioning
confidence: 97%
“…Currently, nearly complete mitochondrial genomes from Vespidae, Eumenidae, Formicidae and Mutillidae have been sequenced respectively within Vespoidea. In the sequenced mitochondrial genomes of Vespoidea, tRNA gene rearrangement was reported; however, rearrangement of protein-coding genes has not been found [22,34,35,36]. A locus of mitochondrial genes comprising cox1 and adjacent tRNA genes was sequenced from representatives of the major clades of Pompilidae and the rearrangement of the trnC and trnY genes was found in the sequenced segments [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 13 proteincoding genes, the initiation codons ATC was found in one, ATG in four, ATT in five, and ATA in three genes, while TAA was the termination codon in all these genes. Phylogenetic analysis using the 13 mitochondrial protein-coding genes from seven closely related taxa of Vespidae (Cameron et al 2008;Song et al 2016;Wei et al 2016;Zhou et al 2016) suggested a sister relationship between V. velutina and V. bicolor (Archer 2012;Chen et al 2016).…”
mentioning
confidence: 99%